Modified Carda Fruit Cocktail Drink Using Captikus - Mercy A. , Mercy A.; Tolosang, Evi Carmela; Lasut, Inka Amanda (International Journal of Strategic Studies, 2025)
Drinks are a basic need for humans in everyday life. Of course, humans need fluids to replenish their bodies. Many of us want to enjoy various kinds of drinks that taste fresh, bitter, and so on. Captikus is one of the drinks that has existed since ancient times and is known by people of all ages. Captikus is also one of the most in-demand drinks among many groups, both young and old, of different genders. Seeing the potential of Captikus drinks, nutmeg juice, and marjan syrup, the research team decided to modify these ingredients into a cocktail, creating a breakthrough in the industrial world. The research method used is the Design Method and the Experimental Method. This method aims to produce unique and interesting new things. From the results of this study, this drink can be combined with other ingredients, such as marjan syrup and nutmeg juice. After several trials, the research team succeeded in creating a new flavor variant, "Carda Fruit," with higher taste and aroma, and greater market value, making it suitable for marketing to the Food and Beverage Industry.